Jet vectoring using active switching - SATO, Kotaro; SUZUOKA, Taisei; NISHIBE, Koichi; YAMASAKI, Gaku (Journal of Fluid Science and Technology, 2024)
Several studies have focused on jet vectoring and mixing enhancement using continuous jets for the secondary flow. In recent years, studies have applied synthetic jets to secondary flows, wherein the driving source can be easily downsized. However, a method to simultaneously control both the deflection angle and the degree of mixing of the generated flow has not yet been established. Thus, this study proposes a novel nozzle that actively controls the direction and turbulence of the primary jet simultaneously by replacing the facing control port of a conventional flip-flop jet nozzle with compact speakers. Specifically, the control factors considered were the phase difference between the opposing synthetic jets generated by the speakers and the dimensionless frequency of the synthetic jets based on the velocity of the primary flow. The flow field was measured via two-dimensional particle image velocimetry analysis and hot-wire anemometer. Consequently, the influence of the phase difference and dimensionless frequency on the deflection angle and turbulence intensity of the generated flow was investigated. The results indicated that the deflection angle of the generated flow could be controlled by adjusting only the phase difference even for the same dimensionless frequency under specific conditions. Furthermore, optimizing the dimensionless frequency by introducing the phase difference facilitated efficient operation with reduced power consumption. In addition, while controlling the deflection angle by the dimensionless frequency and phase difference, the cross-stream distribution of turbulence intensity could be selected at the set deflection angle, subject to limited restrictions. Thus, the results of this study confirm the feasibility of simultaneously controlling the deflection angle and turbulence intensity of the generated flow.